Global Warming – An Astronomical Phenomenon without Connection with Greenhouse Gases in Earth’s Atmosphere? - Takuchev, Nikolay Petrov (European Journal of Applied Sciences, 2025)
The now generally accepted paradigm points to greenhouse gases as the source of global warming, a significant part of which is anthropogenic, from the extraction and burning of fossil fuels and intensive agricultural production. The hope is that it is within humanity’s ability to limit this biosphere-threatening process by regulating the mentioned activities. This article argues that processes on the Sun have partly or entirely caused global warming in the Earth’s atmosphere over the past 70 years. Global warming is likely a consequence of streams of positively charged, high-energy particles emitted by the Sun, mainly during the “rise” phase of solar activity when the phenomena on the Sun’s surface are associated with the growing magnetic field. Part of the flow of high-energy radiation reaches the Earth. It penetrates deep into the Earth’s atmosphere, creating an increased content of ions that serve as condensation nuclei around which water vapor forms drops. Condensation nuclei increase cloudiness in the lower atmosphere. The upper surface of clouds and fog partly reflects electromagnetic solar radiation into space. It does not reach the Earth’s surface, which leads to a decrease in the temperature of the surface and, hence, in the temperature of the ground air heated by the surface. When the solar activity decreases, as observed in the last 70 years, the reverse process occurs – the high-energy fluxes of corpuscular radiation decrease, the ionization of the air in the Earth’s atmosphere decreases, the cloudiness decreases, more solar electromagnetic radiation reaches the Earth’s surface and increases the temperature (Global warming). Significance statement: Global warming – what is this phenomenon threatening humanity, and can we fight it? It seems that humanity has accepted as true the answer that the phenomenon is due to the release of greenhouse gases, and if we stop emitting them, global warming will end. For this purpose, the world allocates about 3 trillion dollars annually. Are these funds being directed correctly? The answer in this article is negative – the phenomenon has a natural cosmic origin, and its consequences can be mitigated through measures different from those applied so far.